ASOSIASI KARAKTERISTIK CEO TERHADAP POTENSI KESULITAN KEUANGAN PERUSAHAAN - Tanjaya, Felix Leonardo; Santoso, Eko Budi (Accounting Study Program, Universitas Ciputra Surabaya, 2020)
This study aims to determine the effect of CEO characteristics interms of facial masculinity, education, and experience to potential of financialdistress. Facial masculinity was measured using dummy variables consistingof masculinity and feminism. Education was measured using dummyvariables of educational level; meanwhile, experience was measured usingdummy variables from CEO work experience. This research used quantitativewith secondary data types taken from annual reports of non-financialcompanies that are listed on Indonesia Stock Exchange. The sampling methodused purposive sampling with the observation period of 2016–2018 andobtained a total sample of 259 samples. The method data analysis usedmultiple linear regression analysis. The result showed that: (1) CEO facemasculinity did not affect financial distress, (2) CEO education did notaffect financial distress, (3) CEO experience positively influenced financialdistress. The results showed the fact that CEO experience is an importantfactor that could improved company performance for avoiding financialdistress potential.